Analysis of the Impact of Fund Withdrawals by the Central Leadership of Muhammadiyah on Bank Syariah Indonesia (BSI) - Solin, Naia Fingkani; Kusmilawaty, Kusmilawaty; Anggraini, Tuti (Amkop Management Accounting Review (AMAR), 2025)
Muhammadiyah is the largest religious organization in Indonesia that has relationships with Islamic financial institutions, including Bank Syariah Indonesia (BSI). The main issue in this study is the tension between religious institutions and Islamic financial institutions. Therefore, this research aims to analyze the impact of fund withdrawals by Muhammadiyah on BSI as the largest national Islamic bank in Indonesia. This study uses a descriptive qualitative method with documentation studies on secondary data, including financial reports, official news, and relevant academic publications. The results show that Muhammadiyah’s fund withdrawal affects BSI’s Third Party Funds (DPK) position and the financing-to-DPK ratio, while the most significant impact is on BSI’s institutional image and public trust in Islamic banking in general. Thus, Muhammadiyah’s decision to withdraw its funds from BSI has strategic implications for the national Islamic financial ecosystem.